Retrospective analysis of the lifetime endocrine response of southern right whale calves to gull wounding and harassment: A baleen hormone approach - Fernández Ajó, Alejandro A.; Hunt, Kathleen E.; Giese, Adriana Carolina; Sironi, Mariano; Uhart, Marcela María; Rowntree, Victoria J.; Marón, Carina Flavia; Dillon, Danielle; DiMartino, Matias; Buck, C. Loren (General and Comparative Endocrinology)
Physiological measurements are informative in assessing the relative importance of stressors that potentially impact the health of wildlife. Kelp Gulls, Larus dominicanus (KG), resident to the region of Península Valdés, Argentina, have developed a unique behavior of landing on the backs of southern right whale adults and calves, Eubalaena australis (SRW), where they feed on their skin and blubber. This parasitic behavior results in large open wounds on the dorsal surface of the whale. Coincidently, the SRW population off the coast of Península Valdés has experienced elevated calf mortality. We quantified levels of glucocorticoids and thyroid hormone extracted from baleen of dead calves to evaluate, retrospectively, the endocrine response of whale calves to gull wounding and harassment. Baleen accumulates hormones as it grows, allowing evaluation of long-term trends in physiological condition. While glucocorticoids (GCs) are known to increase in response to stressors such as disturbance, the metabolic hormone triiodothyronine (T3) has been shown to decrease under sustained food deprivation but is largely unaffected by disturbance stress. We quantified lifetime patterns of GCs and T3 in baleen recovered at necropsy from 36 southern right whale calves with varying severity of wounding from KGs. GC levels in baleen correlated positively with the degree of wounding, while T3 levels remained stable irrespective of the severity of the wounding. Our results suggest no evidence of malnutrition in low vs. severely wounded whales. However, the positive correlation of GCs with wound severity indicates that heavily wounded calves are suffering high levels of physiological stress before they die. This suggests that KG wounding may have contributed to the high southern right whale calf mortality observed in the Península Valdés region of Argentina. Fil: Fernández Ajó, Alejandro A. Northern Arizona University; Estados Unidos Fil: Hunt, Kathleen E. George Mason University; Estados Unidos Fil: Giese, Adriana Carolina. ...